1970
DOI: 10.1002/ange.19700821102
|View full text |Cite
|
Sign up to set email alerts
|

Neuartige Kohlenstoffe

Abstract: In jüngerer Zeit wurde eine Reihe neuartiger Werkstoffe aus Kohlenstoff entwickelt, die dank ihrer einzigartigen Eigenschaften vielfältige Anwendung finden: Pyrographitkörper sind ausgezeichnete elektrische und thermische Leiter in Richtung der Oberfläche, senkrecht dazu sind sie Halbleiter. Eine ähnliche Anisotropie zeigen die Graphitfolien, die ebenfalls gasdicht, aber auch sehr flexibel sind. Der gleichfalls gasdichte glasartige Kohlenstoff ist dagegen völlig isotrop. Schaumkohlenstoff und Kohlenstoffilze s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1980
1980
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…More than a thousand original papers and reviews on this topic have been reported. Carbon exhibits a very rich structural and surface chemistry. ,, Various different architectures are possible because carbon can bind in linear (sp), trigonal (sp 2 ), and tetrahedral (sp 3 ) coordinations. Many crystalline and amorphous forms have been synthesized, such as glassy carbon, fibers, films, and nanotubes. ,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than a thousand original papers and reviews on this topic have been reported. Carbon exhibits a very rich structural and surface chemistry. ,, Various different architectures are possible because carbon can bind in linear (sp), trigonal (sp 2 ), and tetrahedral (sp 3 ) coordinations. Many crystalline and amorphous forms have been synthesized, such as glassy carbon, fibers, films, and nanotubes. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Silica−carbon composite materials are very interesting because of their high electrical conductivity, intercalating capability, high thermal stability, and high resistance to organic solvents. Hybrid materials consisting of a graphite-like carbon phase and an inorganic oxidic component can be synthesized by different strategies. A convenient route for synthesizing the carbon component is the thermal transformation of a suitable organic precursor polymer into the carbon phase. Interpenetrating carbon/silica hybrid materials have been obtained by a sol−gel process of tetraalkoxysilanes using water-soluble monomers or oligomers, which are suitable as carbon precursor materials. , These materials are important for various applications, because each component serves as the template for the other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…halo gênios, oxigênio, nitrogênio) da matriz polimérica por aquecimento, formando uma estrutura aromática extensa [96][97][98][99][100], que eventualmente se aproxima a do grafite [101][102][103]. Estas estruturas conjugadas aumentam a mobilidade e o número dos carregadores de carga, através da formação de radicais livres, gerando cátions ou ânions [104][105][106] pois permite a polimerização do acetileno à temperatura ambiente e pressão atmosférica.…”
Section: Piróliseunclassified
“…Οι αντιδράσεις που λαμβάνουν χώρα είναι : α) απομάκρυνση της φυσικής υγρασίας της ίνας σε θερμοκρασία 100°C, β) απομάκρυνση της χημικά ροφημένης υγρασίας στην ίνα σε θερμοκρασία πάνω από 240°C, γ) διάσπαση των δεσμών C-C, C-0 μέσα στους δακτυλίους με ταυτόχρονη έκλυση νερού, μονοξειδίου και διοξειδίου του άνθρακα με συνέπεια την αλλαγή της μοριακής δομής της κυτταρίνης, δ) σχηματισμός αρωματικών δακτυλίων ή δημιουργία στοιβάδων παρόμοιων του γραφίτη σε θερμοκρασίες από 400-700°C. Η θερμική επεξεργασία μπορεί να συνεχιστεί και σε θερμοκρασίες πάνω από 2000°C (178)(179)(180)(181)(182).…”
Section: παραγωγή ινών άνθρακα με πρόδρομο υλικό την κυτταρίνηunclassified